Investigating the Phytochemical Composition and Antimicrobial Activity of Leaves of Plumeria Rubra Linn - Goyal, Kamal; Mittal, Sanjeev; Gupta, Vikas; Goyal, Ravi Kumar (Journal of Neonatal Surgery, 2025)
From the studies that carried out under this title it is clear that plant may have good phytoconstituents like flavonoids, carbohydrates, phenols, tannins. The present study reveals the in- vitro antimicrobial activity of ethanol and ethyl acetate extract of Plumeria rubra leaves has been evaluated using Disc- diffusion method against Staphylococcus aureus with best inhibition zone (11.22 mm) ethanol extract, Bacillus subtilis (16.22 mm) ethyl acetate extract, Escherichia coli and Pseudomonas aeruginosa of bacterial strains and Aspergillus flavus and Candida albicans of fungal strains showed near about same antifungal activity at the given highest concentration of 8000µg/ml with specific standard Ciprofloxacin and Fluconazole respectively